(untitled) (Teología, 2017)
The theology of liberation has said of itself to constitute a new way of doing theology. In this article we study the thoughts of Jesus Herrera Aceves, Pedro Trigo and Carlos Mesters. It will be seen that the greatest novelty of this is not the use of the hermeneutical circle between the word of God and the historical situation of the poor, but in a new conception of revelation that lies in the recognition of a current revelation of God in the historical events and in the life of the poor. History, that of Jesus and ours, as a hermeneutic place, can also be considered as a theological place of its own.